Development of a Problem-Based Learning E-Module to Enhance Mathematical Literacy Skills through Data Presentation - Musaad, Faida; Sulisworo, Dwi (Universitas Ahmad Dahlan, 2023)
This study discusses the low mathematical literacy skills of students at Junior High School IT Al-Izzah Sorong City, particularly in the area of data presentation. The causes are attributed to ineffective conventional teaching methods and inadequate teaching materials. The research aims to develop a Problem-Based Learning (PBL) e-module to enhance mathematical literacy skills. Through the Research and Development (R&D) approach using the ADDIE model, the study produced an e-module validated for both media and content. Students' response to the e-module was highly positive, indicating a high level of comfort. Analysis showed that the PBL-based e-module effectively improves students' mathematical literacy skills. Despite limitations in access to Android devices, it did not hinder the learning process.